Highly Efficient Nanoscale Analysis of Plant Stomata and Cell Surface Using Polyaddition Silicone Rubber - He, Yi; Zhou, Kaiyue; Wu, Zhemin; Li, Boxiu; Fu, Junliang; Lin, Chinho; Jiang, Dean (Frontiers in Plant Science, 2019)
Stomata are one of the most important physiological apparatus in higher plants, which control gas exchange and water transpiration. The regulation of stomatal aperture is closely coordinated with photosynthesis, uptake of nutrients, plant growth and development and so on. With the development of electron microscope, the high-resolution images of plant stomata and cell surface can be got on the detached plant tissues by scanning electron microscope. However, this method cannot allow us to rapidly analysis the dynamic variation of plant stomata in situ under nondestructive condition. Here, we show a novel plant surface impression technique (PSIT) that can make us to precisely analysis the plant stomata and cell surface. Using this method, we successfully monitored the dynamic variation of stomata and observed the microstructure of soybean leaf trichomes and dragonfly wing at nano-scale. Our results indicate the PSIT can be widely applied to many fields of research.